Problem of prescribing anticoagulant therapy in patients with atrial fibrillation on the regional level - M. G. Nazarkina; V. V. Stolyarova; D. A. Karpova (Медицинский совет, 2020)
Introduction. Cardiovascular diseases are the leading cause of morbidity and mortality worldwide, with heart rhythm disorders accounting for a significant proportion of them. Atrial fibrillation (AF) is an arrhythmia that poses a risk of thromboembolic complications and is difficult to treat with ongoing preventive anticoagulant therapy. Aim of the study. To analyze the prescription of anticoagulant therapy to patients with AF on the regional level. Methods and results. The study included 72 patients with the nonvalvular form of AF (from 41 to 82 years old) of the Department of Rhythm and Conductivity Abnormalities of the State Budgetary Institution of the Republic of Mordovia RCH № 4 for 2019. Three groups were singled out depending on the AF form: the first one – patients with the constant form (n = 22), the second one (n = 24) – with the persistent form, the third one (n = 24) – with the paroxysmal form. The risk of thromboembolic complications was assessed using the CHA2DS2-VASc scale and hemorrhagic complications using the HAS-BLED scale. All patients had a high risk of thromboembolism (index above 2 points), which reflects multiple risk factors and indicates the need for oral anticoagulants (OAC). According to HAS-BLED scale calculations, the risk of haemorrhagic complications was low in most patients (2 or less points) – there was no significant increase in the risk of bleeding, but careful monitoring is required. Analysis of the results revealed that only 54% of patients took OAC, despite the fact that all patients were shown anticoagulant therapy. When analyzing the cases of patients who did not take anticoagulants, it was found that 23% of patients, despite the doctor’s recommendations, refused to take the drugs, 47% of patients justified the inability to control IHR and 30% were unable to purchase expensive new OAC. Conclusion. Despite the recommendations for the management of patients with atrial fibrillation, only 54% were prescribed oral anticoagulants.